The Implementation of Open Door Policy in Dealing with the Syrian Refugee Crisis (A Case Study of Turkey- European Union Cooperation through the Emergency Social Safety Net Program 2016-2017) - Agestia, Ninda Rhetalola; ARUNI, AYU; Nau, Novriest Umbu Walangara (Journal Of Middle East and Islamic Studies, 2023)
Turkey has been greatly impacted by the Syrian crisis. Its geographical proximity leads Turkey to become the main destination for Syrian refugees since the beginning of the crisis. This has resulted various changes in Turkey's political, social, and economic structures. The presence of Syrian refugees has become a turning point for Turkey in its relationship with the European Union, notably the implementation of the Open Door Policy. The European Union offered assistance to share the charge of this particular policy with Turkey regarding Syrian refugees. The EU's humanitarian program, represented by the Emergency Social Safety Net (ESSN) scheme, provides social assistance in the form of debit cards to meet the basic needs of Syrian refugees. This research uses qualitative research methods based on case studies and data collected from literature reviews. The aim of this study is to explain the Emergency Social Safety Net (ESSN) program as a response to the humanitarian needs of Syrian refugees in Turkey and the EU's migration control policy instrument with the implementation of the Open Door Policy.